1999
DOI: 10.1007/s004210050508
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory responses in humans during exercise after exposure to two different light intensities

Abstract: The effects after exposure to two different light intensities (dim, 50 lx and bright, 5000 lx) on thermoregulatory responses during exercise in a climatic chamber (27 degrees C, 60% relative humidity) were studied in nine untrained female subjects, aged 19-22 years. The subjects were in either the dim or bright light intensities from 0600 hours to 1200 hours. They were then instructed to exercise on a cycle ergometer at an intensity of 60% maximal oxygen uptake from 1200 hours to 1300 hours in a light intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Core temperature was monitored with a disposable rectal probe (Monatherm, Mallinckrodt Medical, St. Louis, MO, USA) inserted at least 12 cm beyond the anal sphincter before testing (O'Brien et al, 2000;Zhang & Tokura, 1999). Skin temperatures were monitored with skin thermistors (Grant Instruments Ltd, Cambridgeshire) attached to the left side of the body at four sites (chest, forearm, quadriceps, and calf) using adhesive tape.…”
Section: Recovery Strategiesmentioning
confidence: 99%
“…Core temperature was monitored with a disposable rectal probe (Monatherm, Mallinckrodt Medical, St. Louis, MO, USA) inserted at least 12 cm beyond the anal sphincter before testing (O'Brien et al, 2000;Zhang & Tokura, 1999). Skin temperatures were monitored with skin thermistors (Grant Instruments Ltd, Cambridgeshire) attached to the left side of the body at four sites (chest, forearm, quadriceps, and calf) using adhesive tape.…”
Section: Recovery Strategiesmentioning
confidence: 99%
“…In a case report, an average weight loss of 1.5 to 2 kg was noted in three obese women after 6 weeks of 1 hour of bright light therapy without exercise (31). Another study of nine female subjects found that body mass loss after exercise was significantly greater after exposure to bright light therapy (32). These researchers also observed that the exercise‐induced increases of core body temperature and the production of lactic acid were lower in the bright light condition.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies have involved an examination of the effects of light on body temperature measured at rest and during exercise. Zhang and Tokura [29] exposed participants to bright (5000 lux) light from 06:00 -12:00 hours, and found that core body temperature at the end of a subsequent bout of exercise was significantly lower compared to that in dim light. Aizawa and Tokura [1] also exposed participants to either dim or bright light throughout the morning period and found, again, a significant reduction in body temperature at rest following bright light exposure.…”
mentioning
confidence: 99%